The Effect of Learning Method and Self-Confidence on Student Learning Outcomes - Asep Awaludin; Yayat Ruhiat; Nurul Anriani; Suryadi Suryadi (IJORER : International Journal of Recent Educational Research, 2024)
Objective: This study examines the disparities in enhancing student learning outcomes based on learning methods and varying levels of student self-confidence, categorized as high, medium, and low. Method: This study employs quantitative methodologies utilizing quasi-experimental methods. The study uses a non-equivalent control group technique and follows a 2 x 3 two-way ANOVA factorial design. The study sample comprised 1000 students enrolled at the health Polytechnic Banten, an educational institution in Indonesia. The enormity of this scale requires the study to be divided into many portions due to the significant temporal and financial resources needed. Therefore, a sample size of 10.00% of the population was chosen. In addition, the researchers utilized a systematic random sampling method to determine the number of students involved in the study. Results: The research findings can be classified into three main areas. Firstly, there were significant differences in student learning outcomes between those taught using STEM learning methods and those who received bedside teaching. Secondly, variations in student self-confidence levels (high, medium, and low) also resulted in differences in learning outcomes. Lastly, an interaction was observed between the learning methods and the levels of student self-confidence, which influenced the overall learning outcomes as measured by the average pre-test and post-test scores and questionnaires. Novelty: The novelty of this research was variations from previous research in terms of emphasis, subject, results, and combination of research variables. Previous research only concentrated on STEM methods and self-confidence to improve student learning outcomes. Previous research only examined one research variable: STEM, bedside teaching method, and self-confidence.